Compensation of transducer element positions in a ring array ultrasonic computer tomography system. (30th June 2015) - Tamano, Satoshi; Azuma, Takashi; Imoto, Haruka; Takagi, Shu; Umemura, Shin-Ichiro; Matsumoto, Yoichiro
Abstract: An ultrasonic ring array system was newly developed and ultrasonic computer tomography (USCT) image reconstruction was performed. The USCT transducer of 104 mm diameter had a center frequency of 1.75 MHz and a −6 dB transmit and receive two-way fractional bandwidth of 66%. It had a full 360° circumference divided into four blocks, each of which had 256 elements. All 1024 elements were connected to a high-voltage multiplexer IC. The potential problem of image degradation, which might have been caused by insufficient alignment accuracy between the blocks, was solved by fitting and compensating the delay due to the misalignment. This resulted in a measured transmit and receive beam width of 0.20 mm, which is close to the theoretical value.